PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. TERMINAL TELUK LAMONG SURABAYA - Faisal Yoga Restukumala; Indra Prasetyo (Jurnal Manajerial Bisnis, 2023)
The research aims to determine and analyze the influence of leadership style, work discipline and organizational culture on the performance of PT. Teluk Lamong Terminal, Surabaya. This type of research is explanatory research with a quantitative approach. The research population is all employees as much as 98 people. The sampling technique uses a saturated sample so that the sample in this study is 98, hereinafter referred to as respondents. The results showed both partially and simultaneously leadership style, work discipline and organizational culture on the performance of employees of PT. Teluk Lamong Terminal, Surabaya.